On the application of the Wildman-Crippen model to ionic liquids - Spyridon Koutsoumpos; Myrto Chronaki; Christos Tsonos; Theodoros Karakasidis; Lorenzo Guazzelli; Andrea Mezzetta; Konstantinos Moutzouris (Results in Materials, 2022)
Molar refractivity is the macroscopic analogue of polarizability, an additive property with microscopic interpretation, related to the density and the refractive index of a compound via the Clausius-Mossotti equation. Semiempirical models exploit the additivity by defining atomic, or sometimes group contributions to molar refractivity, eliminating one unknown from the Clausius-Mossotti equation. A very successful model in that regard is the Wildman-Crippen model. Although originally conceived for neutral compounds, we show with specific examples and comparisons that this model is applicable to ionic liquids and amenable to extensions that would further improve its accuracy and generality.